PENGARUH DISIPLIN KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DUTA DIMENSI BATAM - Afisah Cindy; Indarti Sri; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The study aims to analyze the variable impact of job discipline, motivation and work environment on employee performance. The study was done on the PT. Duta Dimensi Batam. In this study are four variables: one common variable and three free variables. Such variables are employee performance (Y), work discipline (X1), motivation (X2), and work environment (X3). The study was conducted using the slovin method where the sample number was 89. The method of analysis used is the testing of quantifying (validity and religious testing), the systematic systematic systematic of quantitative desensitizing analysis, the systematic analysis and simultaneous linear analyssion analysis with the help of version 20's SPSS (statistical package of social science). Research shows that job discipline has a positive and significant impact on performance, motivations have a positive and significant impact on performance. Work environments affect employees' performance simultaneously.Keywords: work discipline, motivation, work environment, employee performance